Human Resources Training in Welcoming the Digitalization of Administration System in Batu Bulek Village, West Sumatra - Desnita desnita; ratnawulan ratnawulan; asrizal asrizal; akmam akmam; ahmad fauzi; fatni mufid (Pelita Eksakta, 2026)
Along with the advancement of the times and the demands for integrated, unified, and fast services, the Regional Government has issued a digital government management system policy at the village level. However, its management has not been optimal at the Batu Bulek Village Head's Office, North Lintau Buo District, Tanah Datar Regency, West Sumatra. The first problem is the limited capacity of village government human resources to manage the ADM system and digital services. This community service activity aims to provide mentoring and coaching to improve the capacity of Batu Bulek Village government human resources to manage the village digital system. Mentoring and coaching are carried out by providing training to village officials, especially on the introduction and how to use the village website. The results of the community service show that the human resource capacity of village officials has increased, especially in managing the Batu Bulek village website.